A Mixed Reality Interface for a Digital Twin Based Crane - Xinyi Tu; Juuso Autiosalo; Adnane Jadid; Kari Tammi; Gudrun Klinker (Applied Sciences, 2021)
Digital twin technology empowers the digital transformation of the industrial world with an increasing amount of data, which meanwhile creates a challenging context for designing a human–machine interface (HMI) for operating machines. This work aims at creating an HMI for digital twin based services. With an industrial crane platform as a case study, we presented a mixed reality (MR) application running on a Microsoft HoloLens 1 device. The application, consisting of visualization, interaction, communication, and registration modules, allowed crane operators to both monitor the crane status and control its movement through interactive holograms and bi-directional data communication, with enhanced mobility thanks to spatial registration and tracking of the MR environment. The prototype was quantitatively evaluated regarding the control accuracy in 20 measurements following a step-by-step protocol that we defined to standardize the measurement procedure. The results suggested that the differences between the target and actual positions were within the 10 cm range in three dimensions, which were considered sufficiently small regarding the typical crane operation use case of logistics purposes and could be improved with the adoption of robust registration and tracking techniques in our future work.